Efficacy of different bio-rationals against Papaya mealybug Paracoccus marginatus (Hemiptera: Pseudococcidae) - Piragalathan, A.; Pakeerathan, K.; Mikunthan, G. (1stRuhuna International Science & Technology Conference, 2014)
Papaw mealybug, Paracoccus marginatus causes severe economic losses in crops mainly in papaw, Carica papaya. Due to its damage, following symptoms such as yellowing, crinckling and distortion of leaves, sooty mould development were found and yield losses was resulted due to its heavy feeding. Considering the seriousness of the damage and safety of the environment, six bio-rationales such as fermented neem leaves solution (1 g/ml), neem leaf extract (20g/ml), Pavetta leaf extract (20g/ml), garlic extract (20g/ml), vermi wash and fermented cow urine (100% V/V) were tested for their efficacy on P. marginatus in the laboratory. These bio-rationales were applied by using hand sprayer on the P. marginatus infested fruits. Mortality percentage of P. marginatus was assessed after 0.5 hr, 3 hr, 6 hr, 24 hr and 48 hr of exposure. The experiment was carried out at a temperature of 28±1°C and 75% Relative humidity and it was designed according to complete randomized design (CRD) with four replicates. Garlic bulb extract, Pavetta leaf extract and fermented cow urine suppressed significantly the highest effect among the six bio-rationals. Garlic bulb extract, Pavetta leaf extract and fermented cow urine gave 87.9%, 83.3%, 75.8% mortality of P. marginatus, respectively after 48 hours of exposure. All six bio-rationals had given more than 50% control in 48 hours of exposure and provided eco-friendly management against P. marginatus. This information is useful to manage the papaw mealy bug using eco-friendly manner
Keywords: Paracoccus Marginatus; Bio-Rationals; Garlic Bulb Extract; Pavetta Leaf Extract